Study on alkalophilic and halophilic microorganisms in the sea waters of northern Vietnam gulf - Hy, Le Gia; Tung, Lai Thanh; Bich Hop, Pham Thi (Academia Journal of Biology, 2014)
The use of enzymes in industry and food process has been extended rapidly. Proteases are used in many industrial applications, such as detergent production, milk processing, fish sauce production etc. Especially, the alkaline and saline-stable enzymes as complement into detergents for sea and brackish-water areas are of great interest. Therefore, studies on the distribution of alkalophilic and halophilic bacteria in the sea and coastal areas, screening of the desired strains and optimization of the enzyme production conditions are necessary. The results of this study showed that samples collected from the Northern Vietnam gulf and coastal areas contained mainly aerobic bacteria at the concentrations up to 4.105 CFU/ml. Other groups, including anaerobic bacteria, actinomycetes and fungi were present at lower concentrations. Yeasts were found with the lowest count. The morphological and physiological characteristics of the isolates have been studied and the results indicated to the great diversity of our marine microflora. Fifty bacteria were tested for the ability to grow in alkaline media, where 3 strains grew very well and other 27 strains grew well. The rest showed poor to normal growth. Eight bacteria (SS-4, SS-6, DS-3, BL-1, CL3-1, CL3-5, MC-3 and QL-1) were topped for the tolerance of alkaline (pH = 10) and saline conditions (NaCl 20%). Of them, the strain MC-3 was selected for further study on the production of alkaline protease.